Micropropagation of Acacia mangium x A. auriculiformis hybrids - Galiana, Antoine; Goh, Dorenn Kim Soh; Chevallier, Marie-Hélène; Gidiman, Jikos; Moo, Hanna; Hattah, M.; Japarudin, Yani (BOIS & FORETS DES TROPIQUES, 2003)
Le résumé en français est disponible dans le fichier PDF de l'article. Acacia mangium x A. auriculiformis is a promising hybrid for tree plantations. It can, however, only be propagated vegetatively, and there is currently a lack of available plant material and expertise concerning its clonal propagation. The authors combined conventional and in vitro propagation methods and demonstrated that largescale reforestation is possible with this hybrid. (Résumé d'auteur)